Perbedaan Perilaku Pasien Diabetes Mellitus Pria dan Wanita dalam Mematuhi Pelaksanaan Diet - Darusman Darusman (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Diabetes melitus  is  one  of  the  degenerative  disease, which  is  the  amount will  increase  in  the future  and needs  serious  treatment  because  of  complications cause  it. Diet  is  the main  therapy  to  improve  and maintain  the  blood sugar  in normal  rate. For helping  the diabetic  patient doing  the  new diet  therapy  in  their daily living  is depend  on  their  attitude and  behavior. The  long  lasting  obedience  in  preparing  the meals  is  one of  the most challenge  in diet  therapy.Method: The  aim  of  this  research  is  for  identificated  the  differences  of  behavior and  the  obedience  between male  and  female who have  diabetes melitus  in diet  therapy with  descriptive comparative  and  independent  t-test with SPSS  version  12.0,Result: The  result of  this  research shows 55,0% males and 70,0%  females have bad behavior of  the obedience in  diet  therapy. Beside  that  80,0% males  and  70,0%  females are  obey  to  follow diet  therapyConclusion: From the  result of  this research shows P = 0,093, because P > 0,05,  the conclusions  is there  is no differences of  behavior  in  obedience diet  therapy between male  and  female.Keywords:  behavior,  obedience,  diet, diabetes melitus